Graphite-containing refractory and steel vessel equipped with graphite-containing refractory
A graphite-containing refractory with a carbon fiber fabric embedded in steelmaking vessels enhances durability by improving fracture energy, addressing the durability issues of existing refractories under severe temperature fluctuations.
Patent Information
- Application Number
- JP2022034466
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-03-07
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2042-03-07
AI Technical Summary
Existing refractories used in steelmaking vessels, such as converters and hot metal pretreatment containers, do not provide sufficient durability under harsh conditions with large temperature fluctuations and thermal gradients, leading to reduced lifespan and increased wear.
A graphite-containing refractory with a carbon fiber fabric woven in multiple directions is embedded inside the refractory body, adhered via an adhesive component, with specific spacing and area ratios to enhance fracture energy and durability.
The refractory exhibits high fracture energy and durability, effectively resisting crack formation and wear under extreme temperature changes, particularly in tuyere bricks and other harsh environments.
Smart Images

Figure 0007619306000017 
Figure 0007619306000018 
Figure 0007619306000019
Abstract
Description
[Technical field]
[0001] The present invention relates to a graphite-containing refractory having a carbon fiber fabric woven from woven carbon fiber bundles disposed inside a refractory body, and to a steel-making vessel (converter, molten iron pretreatment vessel, ladle vessel) incorporating the graphite-containing refractory. [Background technology]
[0002] The equipment used in the iron-making and steel-making processes in steelworks (refining vessels, transport vessels, and other steelmaking vessels) is lined with refractories to withstand long-term use at high temperatures. In general, magnesia-carbon refractories are used for the lining of converters used in the refining process, while alumina-silicon carbide-carbon refractories are used for the lining of torpedoes and blast furnace ladles used in the molten iron pretreatment process. The refractories used for lining these refining vessels and transport vessels are used under extremely harsh conditions, including mechanical shock from the charges, abrasion from stirring of molten steel and molten slag, slag erosion from molten slag, and sudden temperature changes during operation. For this reason, in order to ensure stable operation, it is necessary to use refractories with high durability that can withstand such harsh conditions.
[0003] In particular, the tuyere bricks that make up the tuyere portion of a converter have room temperature gas (oxygen, cooling hydrocarbon gas, etc.) flowing inside, and the inner surface near the inside of the furnace is cooled by the room temperature gas while the outer surface is exposed to high temperatures due to heat transfer from the molten steel in the furnace, so the thermal gradient inside the tuyere bricks is extremely large, and moreover, every time blowing of one charge of the converter is completed, the temperature drops due to the discharge of the molten steel, and large thermal fluctuations are repeated. The tuyere bricks installed in converters are used as frequently as about 2500 to 4000 charges, and are used under extremely harsh conditions where the situation where the above-mentioned large thermal gradient occurs and large thermal fluctuations are repeated for each charge, so they are required to have high durability to withstand use under such conditions. In addition, the refractory linings of the converter other than the tuyere bricks (the bricks that make up the inner wall of the converter) are also used under extremely harsh conditions where large thermal fluctuations as described above are repeated, so they are required to have high durability, although not as high as the tuyere bricks. Similarly, the refractory linings of molten iron pretreatment vessels such as torpedoes and blast furnace ladles, and ladle vessels are required to have high durability because they are used under extremely severe conditions where large thermal fluctuations are repeated.
[0004] As a technology for improving the durability of refractories, Patent Document 1 describes a method of impregnating high-strength fiber bundles with synthetic resin or pitch, and then subjecting them to a hardening process such as heat treatment to obtain a rod-shaped or mesh-shaped solidified body, which is then placed inside the refractory. Since the solidified high-strength fiber bundles are placed inside the refractory without losing their shape, it is said that the mechanical strength and spalling resistance of the refractory can be improved. Patent Document 2 also describes a technique in which a unidirectional bundle or fabric made of fibers having a higher tensile strength than the refractory is bonded to a part or the entire surface of a refractory with a heat-resistant adhesive, and claims that this technique can maintain the refractory at a high strength for a long time, improve the tensile strength of the refractory, suppress cracking and destruction, and improve the life and reliability of the refractory. Specifically, it describes a technique in which a bundle or fabric of fibers is bonded to a nozzle through which molten steel flows, such as a long nozzle, a submerged nozzle, or a sliding nozzle used in a continuous casting process of steel, in a direction that restrains the outer surface of the nozzle, and an oxidation prevention base layer or an oxidation prevention layer is disposed on the surface. In these nozzles, the bundle or fabric of fibers restrains the thermal expansion toward the outer surface when molten steel flows through the nozzle, and compressive stress is generated in the refractory constituting the nozzle, which is thought to suppress the occurrence of cracks and destruction. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2005-320196 A [Patent Document 2] JP 2007-106618 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, as a result of investigations conducted by the present inventors, it was found that even if carbon fibers are arranged in a refractory material in the form shown in Patent Documents 1 and 2, sufficient durability is not obtained for the refractory material to be used in steelmaking vessels (such as converters and molten iron pretreatment vessels) exposed to the harsh conditions described above. In addition, the technology described in Patent Document 1 involves placing a rod-shaped or mesh-shaped solidified body made by solidifying high-strength fiber bundles with resin, pitch, etc. inside a refractory material. Therefore, when the refractory raw materials are molded or constructed by compression molding or pouring, the solidified body acts as resistance, preventing the uniform compression and flow of the refractory raw materials, resulting in a decrease in the strength and breaking energy of the refractory material and a decrease in its durability.
[0007] In addition, in the continuous casting process in which the nozzle described in Patent Document 2 is used, multiple charges of molten steel blown in a converter are continuously cast, so the temperature change cycle of the nozzle used is longer than that of the refractory lining of the converter, hot metal pretreatment vessel, etc., and since the outer surface of the nozzle is subjected to radiation from the molten steel stored in the downstream vessel located below, the temperature difference with the molten steel flowing inside the nozzle is not so large. In contrast, the refractory lining of the converter, hot metal pretreatment vessel, etc. (particularly the tuyere bricks constituting the tuyere part of the converter) is used under very severe conditions as described above, and the inventors have found that the technology described in Patent Document 2 cannot sufficiently improve the durability of such refractories.
[0008] Therefore, an object of the present invention is to solve the above-mentioned problems of the prior art and to provide a graphite-containing refractory which has high durability even when used under conditions where temperature increases and decreases are repeated over a long period of time, such as the lining refractory of a converter or a molten iron pretreatment vessel, and which has high durability even when used under conditions where the internal temperature gradient is very large, such as the tuyere brick of a converter. Another object of the present invention is to provide an iron-making vessel equipped with a graphite-containing refractory having such high durability. [Means for solving the problem]
[0009] As a result of extensive investigations to solve the above problems, the inventors have found that by embedding a specific carbon fiber fabric in a predetermined form inside the refractory, and preferably optimizing the fiber diameter and number of the carbon fibers constituting the carbon fiber fabric, and further the density of the carbon fibers in the cross section of the refractory, the fracture energy of the refractory can be significantly improved compared to conventional techniques, and high durability can be obtained even in the extremely severe usage environments described above. The present invention has been made based on these findings, and has the following gist.
[0010] [1] A graphite-containing refractory having a graphite-containing refractory body (A) and a carbon fiber fabric (B) in which carbon fiber bundles (b) are woven in two or more directions embedded therein, The carbon fiber fabric (B) contains an adhesive component (c) in the carbon fiber bundles (b) and is adhered or in close contact with the refractory body (A) via the adhesive component (c); The carbon fiber bundles (b) arranged in the same direction constituting the carbon fiber fabric (B) have an interval between adjacent carbon fiber bundles (b) that is larger than the maximum particle size of the aggregate constituting the refractory body (A), A graphite-containing refractory, characterized in that in a cross section of the refractory in the plane direction of the carbon fiber fabric (B), the area ratio of the carbon fiber fabric (B) to the cross section of the refractory is 20% or more.
[0011] [2] The graphite-containing refractory according to the above [1], characterized in that a carbon fiber fabric (B) is embedded inside the refractory body (A) along a direction perpendicular to a working surface of the refractory. [3] The graphite-containing refractory according to the above [1] or [2], characterized in that the thickness of the carbon fiber fabric (B) is 0.1 mm or more and 3 mm or less. [4] The graphite-containing refractory according to any one of the above [1] to [3], characterized in that the refractory body (A) has two or more layers of carbon fiber fabric (B) embedded therein at intervals. [5] The graphite-containing refractory according to [4] above, characterized in that two or more layers of the carbon fiber fabric (B) are embedded in parallel at intervals, and the interval between adjacent carbon fiber fabrics (B) is 10 mm or more.
[0012] [6] The graphite-containing refractory according to any one of the above [1] to [5], characterized in that the carbon fiber bundles (b) constituting the carbon fiber fabric (B) in the same direction have an interval between adjacent carbon fiber bundles (b) of more than 3 mm. [7] The graphite-containing refractory according to any one of the above [1] to [6], characterized in that the carbon fiber bundles (b) constituting the carbon fiber fabric (B) have a width of more than 1 mm and not more than 15 mm. [8] The graphite-containing refractory according to any one of the above [1] to [7], wherein the adhesive component (c) is an organic substance having a residual carbon ratio of 6 mass% or more and 80 mass% or less.
[0013] [9] The graphite-containing refractory according to any one of the above [1] to [8], wherein the refractory body (A) has a graphite raw material content of 1 mass% or more and 80 mass% or less.
[10] The graphite-containing refractory according to any one of the above [1] to [9], wherein the refractory body (A) has a magnesia raw material content of 20 mass% or more and 99 mass% or less.
[11] The graphite-containing refractory according to any one of the above [1] to
[10] , wherein the refractory body (A) has an alumina raw material content of 10 mass% or more and 95 mass% or less.
[12] The graphite-containing refractory according to any one of the above [1] to [9] and
[11] , characterized in that the refractory body (A) has a silica raw material content of 1 mass% or more and 50 mass% or less.
[0014]
[13] The graphite-containing refractory according to the above
[11] or
[12] , wherein the refractory body (A) has a silicon carbide raw material content of 1 mass% or more.
[14] The graphite-containing refractory according to any one of the above [1] to
[13] , characterized in that the refractory body (A) contains refractory chips obtained by pulverizing used refractories in an amount of 10% by mass or more and 90% by mass or less as a refractory raw material.
[15] A converter comprising any one of the graphite-containing refractories [1] to
[14] above.
[16] A molten iron pretreatment vessel comprising the graphite-containing refractory material according to any one of [1] to
[14] above.
[17] A ladle vessel comprising any one of the graphite-containing refractory materials [1] to
[14] above. Effect of the Invention
[0015] Since the graphite-containing refractory of the present invention has high fracture energy, it has high durability even when used under conditions where temperature increases and decreases are repeated over a long period of time, such as in the lining refractory material of a converter or a molten iron pretreatment vessel, and it also has high durability even when used under conditions where the internal temperature gradient is very large, such as in the case of a converter tuyere brick. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a schematic diagram showing one embodiment of the graphite-containing refractory of the present invention, in which FIG. 1(A) is a side view, and FIG. 1(B) is a cross-sectional view taken along line II in FIG. 1(A) (a cross-sectional view parallel to the operating surface of the refractory). [Diagram 2]Cross-sectional view along line II-II in Figure 1(A) (cross-sectional view of the refractory in the plane direction of carbon fiber fabric B) [Diagram 3] FIG. 1 is a flow chart showing an example of a process for producing the graphite-containing refractory material of the present invention. [Figure 4] FIG. 4(A) is an explanatory diagram showing a method for measuring the bending strength of a graphite-containing refractory in an embodiment, and FIG. 4(B) is an explanatory diagram showing an end face of a test piece in FIG. 4(A). [Diagram 5] FIG. 1 is a diagram showing an example of fracture energy calculated from a load-displacement curve obtained in a three-point bending strength test in an embodiment. [Figure 6] FIG. 6 shows a test method for evaluating the corrosion resistance of a graphite-containing refractory material in the examples. FIG. 6(A) is an explanatory diagram showing the test furnace and a cylindrical sample in vertical section as the test is carried out. FIG. 6(B) is a plan view of the cylindrical sample shown in FIG. 6(A). FIG. 6(C) is a perspective view showing one of the test pieces constituting the cylindrical sample shown in FIGS. 6(A) and (B). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The graphite-containing refractory of the present invention is a graphite-containing refractory in which a woven carbon fiber fabric B is embedded (disposed) under specific conditions inside a refractory body A containing graphite. 1 and 2 are schematic diagrams showing an embodiment of the graphite-containing refractory of the present invention, in which Fig. 1(A) is a side view and Fig. 1(B) is a cross-sectional view taken along line II in Fig. 1(A) (a cross-sectional view parallel to the refractory working surface), where x is the working surface (y is the counter-working surface) of the refractory. Fig. 2 is a cross-sectional view taken along line II-II in Fig. 1(A) (a cross-sectional view of the refractory in the plane direction of the carbon fiber fabric B). In the graphite-containing refractory of this embodiment, three layers of carbon fiber fabric B are embedded at intervals inside the refractory body A.
[0018] The configuration of the carbon fiber fabric B and the embedding conditions (shape) thereof will be described below. As shown in Fig. 2, the carbon fiber fabric B is a sheet-like member (woven fabric) formed by weaving carbon fiber bundles b in two or more directions (i.e., weaving while oriented in two or more directions). The number of orientations of the carbon fiber bundles b is arbitrary, but the carbon fiber fabric B of this embodiment is formed by weaving the carbon fiber bundles b while oriented in two perpendicular directions. Note that if the orientation direction of the carbon fiber bundles b is in one direction, a carbon fiber fabric cannot be formed, and therefore a graphite-containing refractory material with carbon fiber fabric embedded therein cannot be obtained. The carbon fiber fabric B is embedded (placed) inside the refractory body A, and as shown in the "enlarged cross-sectional view in the width direction of the carbon fiber bundle b" in Figure 2, the adhesive component c is contained within the carbon fiber bundle b, and the carbon fiber fabric B is embedded (placed) in a state of being adhered or adhered to the refractory body A via the adhesive component c.
[0019] Here, the carbon fiber fabric B is integrated into a bundle by containing the carbon fiber bundles b constituting it with the adhesive component c, and is also integrated with the refractory by adhering or bonding to the refractory body A via the adhesive component c, thereby obtaining a high fracture energy capable of suppressing the occurrence of cracks. In particular, when an organic substance (such as an organic resin liquid) having adhesiveness is used as the adhesive that constitutes the adhesive component c, the adhesive (adhesive agent) imparts adhesiveness to the carbon fibers, thereby bundling the carbon fiber bundles b, and when the refractory is molded, the adhesion between the refractory and the carbon fibers can be improved, which is more effective in suppressing defects such as cracks. The preferred conditions for the adhesive component c will be described in detail later.
[0020] The carbon fiber fabric B may be arranged in any manner inside the refractory body A without any particular limitation, but since the tensile stress that causes cracks during operation occurs in the longitudinal direction of the refractory, it is preferable to arrange (embed) it linearly along one direction, and particularly preferable to arrange (embed) it along a direction perpendicular to the refractory operating surface x. The carbon fiber fabric B may be composed of two or more overlapping layers of fabric. The end of the carbon fiber fabric B embedded inside the refractory body A may or may not be exposed on the surface of the refractory body A. In the latter case, on the working surface x side of the refractory, it is preferable that the distance between the end of the carbon fiber fabric B and the working surface x is as small as possible, but on the counter working surface y side, the distance between the end of the carbon fiber fabric B and the counter working surface y may be relatively large. This is because the carbon fiber fabric B does not need to be embedded in the part on the counter working surface y side of the refractory that is expected to remain even after use is finished.
[0021] The carbon fiber bundles b in the same direction (carbon fiber bundles b woven in the same direction) that make up the carbon fiber fabric B are woven so that the interval L (L1, L2 in Fig. 2) between adjacent carbon fiber bundles b is larger than the maximum grain size of the aggregate that makes up the refractory body A. By making the interval L (L1, L2) between the carbon fiber bundles b larger than the maximum grain size of the aggregate raw material in this way, the carbon fiber fabric and the aggregate raw material can be well entangled, and high fracture energy can be maintained without lamination during molding. Here, the interval L between the carbon fiber bundles b is the distance between the outer surfaces of the carbon fiber bundles b, as shown as L1 and L2 in Fig. 2. In addition, the distance L between adjacent carbon fiber bundles b (L1, L2 in FIG. 2) is preferably more than 3 mm. This allows the carbon fiber fabric B to be well entangled with not only the coarse particles but also the fine particles as described above, and also makes it difficult for peeling caused by the carbon fiber bundles, known as lamination, to occur during molding. There is no particular upper limit to this distance L (L1, L2 in FIG. 2), but in view of the relationship with the density of carbon fibers described below, it is generally preferable to set the upper limit at about 50 mm.
[0022] The carbon fiber fabric B is embedded (placed) inside the refractory body A so that the area ratio of the carbon fiber fabric B to the cross-sectional area of the refractory in the plane direction is 20% or more. Here, the area occupied by the carbon fiber fabric B is the area calculated by w1×w2 shown in FIG. 2. By setting the area ratio of the carbon fiber fabric B to the cross-sectional area of the refractory to 20% or more in this way, the fracture energy is increased and crack extension can be appropriately suppressed. From this viewpoint, it is more preferable that the area ratio of the carbon fiber fabric B to the cross-sectional area of the refractory is 40% or more.
[0023] If the thickness of the carbon fiber fabric B is too small, the fracture energy is unlikely to increase, and the crack propagation suppression effect is relatively low. On the other hand, if the thickness is too large, the carbon fiber bundles b constituting the carbon fiber fabric B are likely to spring back (rebound after compression) during molding. For this reason, the thickness of the carbon fiber fabric B is preferably 0.1 mm or more and 3 mm or less. Also, like the graphite-containing refractory of this embodiment, the carbon fiber fabric B is preferably embedded (arranged) in two or more layers at intervals in the thickness direction according to the thickness of the refractory body A. Usually, in this case, two or more layers of the carbon fiber fabric B are embedded in parallel at intervals. In this way, by embedding multiple layers of the carbon fiber fabric B according to the thickness of the refractory body A, the effect of suppressing crack extension due to an increase in fracture energy can be more appropriately obtained. In addition, when two or more layers of carbon fiber fabric B are embedded in parallel with a gap therebetween, if the gap between adjacent carbon fiber fabrics B is too small, springback is likely to occur during molding, so the gap between adjacent carbon fiber fabrics B is preferably 10 mm or more. Here, the gap between adjacent carbon fiber fabrics B refers to the distance between the outer surfaces of the carbon fiber fabrics B.
[0024] In addition, the carbon fiber bundle b constituting the carbon fiber fabric B preferably has a width w of more than 1 mm and not more than 15 mm. Here, the width w of the carbon fiber bundle b refers to the length of the long side or major axis in the cross section of the carbon fiber bundle b in the width direction, as shown in FIG. 2 (however, when the cross section in the width direction is a square or a circle, the length of one side or the diameter). Since the width w of the carbon fiber bundle b is more than 1 mm, the number of carbon fiber bundles b woven together can be reduced when the same number of carbon fibers are used, so that the bulkiness of the carbon fiber fabric B due to the woven carbon fiber bundles b can be suppressed, and the tensile strength unique to the carbon fiber fabric can be utilized. On the other hand, since the width w of the carbon fiber bundle b is 15 mm or less, it is possible to reduce interference between the coarse grain material of the raw material used in the refractory body A and the carbon fiber bundle b, or the melting damage of the carbon fiber bundle b itself can be a trigger for the melting damage of the refractory.
[0025] The carbon fiber fabric used in the present invention is a woven carbon fiber bundle made by bundling carbon fibers. 2 The carbon fiber bundle has a mass per bundle (however, when the carbon fiber fabric is composed of two or more overlapping layers of fabric, the total mass of the overlapping layers of fabric) of about 40 to 1300 g, a fiber diameter of about 1 to 45 μm, and a number of carbon fibers per bundle of about 1000 to 300000. If the number of carbon fibers (existence density) arranged in the refractory body A is too small, the contact area between the refractory raw material and the carbon fiber bundle is small, and the effect of the present invention is relatively reduced, whereas if the number of carbon fibers (existence density) is too large, the carbon fiber bundle is likely to spring back during molding, so that it is preferable that the number of carbon fibers (existence density) arranged in the refractory body A is within an appropriate range. Specifically, the carbon fiber fabric B usually has a density (embedding density) of the carbon fibers constituting the carbon fiber fabric B in a cross section of the refractory in a direction perpendicular to the plane direction of the carbon fiber fabric B (usually a cross section of the refractory parallel to the working surface x of the graphite-containing refractory) of 10 to 2000 fibers / mm 2 It is preferable that the refractory material is embedded in the refractory body A so that the refractory material is approximately 100%.
[0026] As described above, in the present invention, the carbon fiber fabric B embedded (placed) inside the refractory body A must have a spacing between adjacent carbon fiber bundles b larger than the maximum particle size of the aggregate constituting the refractory body A, and the area ratio of the carbon fiber fabric B to the cross-sectional area of the refractory in the surface direction of the carbon fiber fabric B must be 20% or more. Furthermore, by satisfying the following conditions: (i) the thickness of the carbon fiber fabric B is 0.1 mm or more and 3 mm or less, and (ii) the width of the carbon fiber bundles b constituting the carbon fiber fabric B is more than 1 mm and 15 mm or less, the adhesion between the refractory raw material and the carbon fiber fabric is further improved, so that the refractory (brick) is easily densified during molding, and the fracture energy is significantly increased. In addition, the amount of gas escaping from the inside of the refractory when exposed to high temperatures is suppressed, thereby suppressing the occurrence of cracks.
[0027] The adhesive component c is preferably an organic material such as an organic resin and / or inorganic fine particles such as alumina and silica, and in the case of an organic material, the residual carbon rate is preferably 6% by mass or more and 80% by mass or less. When the refractory is used (when the actual machine is in operation), the temperature reaches a high level of 500°C or more (measured at 900°C in JIS K6910) even inside. At this time, even in an environment with almost no oxygen inside, such as a graphite-containing refractory, if the adhesive component c is an organic substance, a part of the adhesive attached to the carbon fiber fabric is gasified by decomposition or evaporation and dissipated outside the refractory. The carbon residue rate is thought to be an index of the weight ratio of the adhesive that remains without being gasified and dissipated, and varies depending on the type and quality of the adhesive. In the present invention, based on the idea that the carbon residue rate of the adhesive affects the fracture energy when a graphite-containing refractory using a carbon fiber fabric is exposed to high temperatures, which is an actual use environment, an investigation was conducted, and it was found that the fracture energy is likely to be high when an adhesive (organic substance) with a carbon residue rate of 6 to 80% by mass is used. This is thought to be because the use of an adhesive (organic substance) with such a specific residual carbon ratio increases the adhesion between the refractory raw material (refractory body A) and the carbon fiber fabric B, making it easier to densify the refractory brick during molding. In addition, the amount of gas that escapes from the inside of the refractory when exposed to high temperatures is suppressed, thereby suppressing the occurrence of cracks and increasing the fracture energy. It was also found that in the present invention, high fracture energy can be obtained when the adhesive component c is inorganic fine particles such as alumina or silica. This is thought to be because, even when inorganic fine particles (especially inorganic fine particles derived from inorganic sol) are used, the adhesion between the refractory raw material (refractory body A) and the carbon fiber fabric B is increased, making it easier to densify the refractory brick during molding, and in addition, when exposed to high temperatures during use, the inorganic fine particles are sintered, suppressing the occurrence of cracks and increasing the fracture energy.
[0028] When the adhesive component c is an organic material, if the carbon content is less than 6% by mass, the amount of gas escaping from the inside of the refractory at high temperatures increases, and many defects such as pores are generated, making it difficult to increase the fracture energy. On the other hand, if the carbon content exceeds 80% by mass, almost no gas escapes from the inside of the refractory at high temperatures, and the refractory becomes too dense and brittle, making it difficult to increase the fracture energy. From the above viewpoints, the carbon content of the organic material is preferably 20 to 80% by mass, and more preferably 40 to 80% by mass. As shown in FIG. 2, the adhesive component c is present (permeates) in the carbon fiber bundles (gaps between the carbon fibers) to integrate the carbon fiber bundles B as a bundle, and also covers the outer surface of the carbon fiber bundles B to bond or adhere the carbon fiber bundles B to the refractory body A. Therefore, it is desirable that the adhesive used is liquid. In addition, the adhesive component c must remain without decomposition or evaporation even at high temperatures, but since combustion by oxygen hardly occurs when used with graphite-containing refractories, it is possible to use a resin that is highly combustible in the presence of oxygen. From these conditions, the adhesive component c is suitable to be one or more selected from organic resins (organic resins derived from organic resin solutions), organic substances derived from tar and / or pitch, organic substances derived from organic pastes, and inorganic fine particles derived from inorganic sols (i.e., any one of these or a mixture of these).
[0029] Therefore, examples of adhesives (tackifiers) that are applied to carbon fiber bundles during production include organic resins (solutions), pitch, tar, organic glue, inorganic sols, etc. Specific examples include phenolic resins, epoxy resins, melamine resins, urea resins, alkyd resins, unsaturated polyester resins, polyurethane resins, thermosetting polyimide resins (resin solutions consisting of one or more of these organic resins), pitch, tar, starch glue, alumina sol, silica sol, zirconia sol, chromia sol, titania sol, magnesia sol, calcia sol, yttria sol, etc., and one or more selected from these can be used. In addition, these adhesives can be thinned with a solvent to adjust the viscosity during manufacturing, but it is desirable to limit the use of solvents (such as water) that gasify even in the absence of oxygen at high temperatures of 500°C or higher to an amount equal to or less than the weight of the adhesive components.
[0030] Next, the composition of the refractory body A will be described. The refractory body A preferably contains 1% by mass or more and 80% by mass or less of graphite raw material. By making the content of the graphite raw material 1% by mass or more, the crack resistance of the graphite-containing refractory can be ensured, and the oxidative loss of the carbon fibers inside the refractory can be suppressed. On the other hand, by making the content of the graphite raw material 80% by mass or less, the oxidative loss of the graphite raw material on the surface of the refractory can be suppressed. As the graphite (carbon raw material), scaly graphite or the like is generally used. As such, refractories in which the refractory body A contains 1 to 80% by mass of graphite raw material include, for example, magnesia-carbon refractories (graphite-containing refractories with magnesia raw material as aggregate), which are refractories mainly composed of magnesia and carbon, alumina-silicon carbide-silica-carbon refractories (graphite-containing refractories with alumina raw material, silicon carbide raw material, and silica raw material as aggregate), which are refractories mainly composed of alumina, silicon carbide, silica, and carbon, and alumina, carbon. Examples include alumina-silicon carbide-carbon refractories (graphite-containing refractories with alumina raw materials and silicon carbide raw materials as aggregate), which are refractories whose main components are silicon carbide and carbon; silica-silicon carbide-carbon refractories (graphite-containing refractories with silica raw materials and silicon carbide raw materials as aggregate), which are refractories whose main components are silica, silicon carbide and carbon; and alumina-silicon carbide-silica-carbon refractories that use refractory scrap as part of the aggregate raw material.
[0031] In general, the lining (including the tuyere) of the converter used in the refining process is made of magnesia-carbonaceous refractories (graphite-containing refractories with magnesia raw materials as aggregate), which are refractories mainly composed of magnesia and carbon. When the refractory body A is a magnesia-carbonaceous refractory, it is preferable that the refractory body A contains 20% to 99% by mass of magnesia raw materials, which suppresses cracking due to thermal spalling and provides a refractory with corrosion resistance that can withstand the erosion of converter slag containing a large amount of FeO. It is preferable to use a high-purity magnesia raw material with a magnesia concentration of 90% by mass or more as the magnesia raw material.
[0032] Generally, the lining of the molten iron pretreatment vessels (torpedoes, blast furnace ladles, etc.) used in the molten iron pretreatment process is made of refractories whose main components are alumina, silicon carbide and carbon, such as alumina-silicon carbide-carbon refractories (graphite-containing refractories with alumina raw materials and silicon carbide raw materials as aggregates) or alumina-silicon carbide-silica-carbon refractories (graphite-containing refractories with alumina raw materials, silicon carbide raw materials and silica raw materials as aggregates), whose main components are alumina, silicon carbide, silica and carbon. When the refractory body A is an alumina-silicon carbide-carbon refractory or an alumina-silicon carbide-silica-carbon refractory, it is preferable that the alumina raw material contains 10% by mass or more and 95% by mass or less of the alumina raw material, which provides high corrosion resistance against the molten iron pretreatment slag and further suppresses the occurrence of cracks due to thermal spalling. Note that it is preferable to use a high-purity alumina raw material with an alumina concentration of 70% by mass or more as the alumina raw material.
[0033] Furthermore, when the refractory body A is an alumina-silicon carbide-carbon refractory or an alumina-silicon carbide-silica-carbon refractory, it is preferable that the refractory body A contains 1% by mass or more of silicon carbide raw material. By containing 1% by mass or more of silicon carbide raw material, oxidation of graphite in the air atmosphere can be suppressed, so that high crack resistance can be maintained. In addition, it is preferable to use a high-purity silicon carbide raw material with a silicon carbide concentration of 80% by mass or more as the silicon carbide raw material. Furthermore, when the refractory body A is an alumina / silicon carbide / silica / carbonaceous refractory, it preferably contains 1% by mass or more and 50% by mass or less of silica raw material, which makes it possible to achieve both high crack resistance and high resistance to corrosion.
[0034] The magnesia-carbon refractories used for lining the converter are used under very severe conditions, such as mechanical impacts from the charge, abrasion due to stirring of molten steel and molten slag, slag erosion by molten slag, and sudden temperature changes during converter operation. For this reason, it is preferable to use magnesia-carbon refractories with high durability that can withstand the severe conditions in order to ensure stable operation. Similarly, alumina-silicon carbide-carbon refractories and alumina-silicon carbide-silica-carbon refractories used for lining the molten pig iron pretreatment vessels such as torpedoes and blast furnace ladles are also used under very severe conditions, so it is preferable to use refractories that can withstand these conditions. According to the present invention, the fracture energy of the graphite-containing refractories used under these very severe conditions is significantly improved compared to conventional graphite-containing refractories, and high durability is obtained.
[0035] Furthermore, when the refractory body A is a silica-silicon carbide-carbonaceous refractory, which is a refractory mainly composed of silica, silicon carbide and carbon, it is preferable that the refractory contains 1% by mass or more of silicon carbide raw material and 1% to 50% by mass of silica raw material, thereby achieving both high crack resistance and high resistance to melting damage. By containing 1% by mass or more of silicon carbide raw material, oxidation of graphite in the air atmosphere can be suppressed, so that high crack resistance can be maintained. Note that it is preferable to use a high-purity silicon carbide raw material with a silicon carbide concentration of 80% by mass or more as the silicon carbide raw material.
[0036] Here, as the alumina raw material, for example, one or more of alumina shale, white alumina, brown alumina, etc. are used. As the silicon carbide raw material, for example, one or more of green silicon carbide, black silicon carbide, etc. are used. As the silica raw material, for example, one or more of aloesite, mullite, etc. are used. The graphite-containing refractory can further contain (mix) a metal powder raw material for the purpose of suppressing the amount of heat radiation from the steelmaking vessel while increasing durability. Examples of the metal powder raw material include metal Si, metal Al, metal Al-Si, Al4SiC4, and B4C, and one or more of these can be contained. The content of the metal powder raw material is not particularly specified, but is usually preferably about 1 to 5 mass%. If the content (mixture amount) of the metal powder raw material is less than 1 mass%, the effect of improving durability by mixing the metal powder raw material cannot be sufficiently obtained, while if it exceeds 5 mass%, the strength becomes too high, so that cracks are likely to occur when used in an actual machine, making the bricks more likely to break, and the number of times it can be used in an actual machine may decrease.
[0037] The refractory body A can contain 10% by mass or more and 90% by mass or less of refractory chips obtained by crushing used refractories as aggregate raw materials. In particular, when the refractory body A is an alumina-silicon carbide-carbon refractory (including alumina-silicon carbide-silica-carbon refractories that further contain a silica raw material; the same applies below), refractory chips obtained by crushing used alumina-silicon carbide-carbon refractories (including alumina-silicon carbide-silica-carbon refractories that further contain a silica raw material; the same applies below) can be suitably used as aggregate raw materials. When refractory waste is contained in this manner, the remainder of the refractory raw material is unused raw material (virgin raw material).
[0038] In the refractory body A made of alumina, silicon carbide, and carbonaceous refractories, when the content of refractory waste obtained by crushing used alumina, silicon carbide, and carbonaceous refractories is 10% by mass or more and 90% by mass or less, the cracking resistance and corrosion resistance are the same as those of a graphite-containing refractory made only of virgin raw materials. The reason for this is that although the purity of the refractory waste raw materials is lower than that of virgin raw materials, by using the refractory waste raw materials in combination with virgin raw materials, a significant decrease in the corrosion resistance of the Al2O3 component in the refractory waste raw materials can be suppressed. However, when the content of the refractory waste is more than 90% by mass, the content of the virgin raw materials is too low, so a significant decrease in the corrosion resistance of the Al2O3 component in the refractory waste raw materials cannot be suppressed. In addition, when the content of the refractory waste is less than 10% by mass, the reuse rate of the refractory waste is too low, so the cost of treating the refractory waste as industrial waste increases significantly.
[0039] Next, the method for producing the graphite-containing refractory material of the present invention will be described. 3 shows an example of a manufacturing process for the graphite-containing refractory of the present invention. In this manufacturing process, an appropriate amount of binder is added to the refractory raw material and kneaded, and the kneaded mixture is filled into a mold together with a carbon fiber fabric in which a specific adhesive has been permeated (impregnated) into the inside of the carbon fiber bundle and attached to the outer surface, and press-molded to obtain a molded refractory product. Examples of binders that can be used include phenol resin (base agent) + hexamine (hardener), carbon bond, and ceramic bond. As a method for filling a mold with the kneaded refractory raw material together with carbon fiber fabric (carbon fiber fabric having an adhesive permeated (impregnated) into the interior of carbon fiber bundles and also adhered to the outer surface; the same applies below), there is, for example, a method in which a certain amount of the kneaded material is charged into the mold, then the carbon fiber fabric is arranged (charged), and a certain amount of the kneaded material is again charged into the mold. Therefore, to produce a graphite-containing refractory having multiple layers of carbon fiber fabric B embedded inside a refractory body A as shown in Figure 1 using this method, a step of charging a certain amount of the kneaded material into the mold, then arranging the carbon fiber fabric on it, and a step of charging a certain amount of the kneaded material on it are repeatedly performed.
[0040] In addition, in order to make the adhesive (tackifier) permeate (impregnate) and adhere to the carbon fiber fabric, for example, the carbon fiber fabric is immersed in a resin (resin solution) or inorganic sol constituting the adhesive, or the resin (resin solution) or inorganic sol constituting the adhesive is sprayed onto the carbon fiber fabric, thereby making the adhesive permeate and adhere to the carbon fiber fabric, and the carbon fiber fabric with the adhesive permeated and adhered thereto is charged into a mold together with the kneaded material in the above-mentioned manner. Here, the adhesive permeated and adhered to the carbon fiber fabric may be in a state where it has a tackiness that allows the carbon fiber fabric and the refractory (kneaded material) to adhere or bond to each other (so-called semi-dried state) even if it has been cured or solidified to some extent when the carbon fiber fabric is placed in the kneaded material. In addition, as another method, the adhesive may be impregnated into the carbon fiber bundle in advance, and then the cured or solidified carbon fiber fabric may be prepared, and the adhesive may be adhered to the outer surface of the carbon fiber fabric again when it is placed in the kneaded material.
[0041] Press molding can be performed using standard die press molding, which compresses in one direction within a die, but CIP molding can also be used, which applies pressure evenly from all directions using a liquid. For shapes where it is difficult to apply even pressure with unidirectional compression, such as shapes with different thicknesses in different parts, it is preferable to use CIP molding, as this reduces bias in the degree of compression depending on the part. The molding process may be performed by a molding method other than press molding. Examples of molding methods other than press molding include molding by pouring, one of which is a method in which an inner frame is installed at the construction site, which is the working surface of a pot or tundish, and an amorphous refractory (refractory raw material) is poured into this inner frame, and the inner frame is removed after drying (drying process) and solidification. There is also a method in which the amorphous refractory (refractory raw material) is poured into a formwork of a refractory shape instead of pouring into the construction site, and the refractory is removed from the formwork after drying (drying process) and solidification, and then transported to the construction site for construction. Although this method requires a lot of work to install the refractory at the construction site, it is preferable because it is easy to embed the carbon fiber fabric when pouring the amorphous refractory into the formwork and to control the temperature during solidification. In these casting methods, carbon fiber fabric is placed inside the inner frame or mold, and then unshaped refractory (raw refractory material) is poured into the inner frame or mold, and then dried (drying process) and solidified.
[0042] The refractory molded product obtained as described above is dried. This drying is usually carried out at about 200 to 230° C. for the purpose of drying (curing) the refractory molded product. In addition, the refractory molded body obtained by the above-mentioned casting is dried and solidified by heating the refractory molded body held in an inner frame installed at the construction site or in a form installed at another location with a heating means such as a heating burner, etc. Thereafter, the inner frame is removed and the molded body is taken out of the form.
[0043] As a result of the above, the graphite-containing refractory of the present invention is obtained, which is a graphite-containing refractory in which carbon fiber fabric B is arranged (embedded) under specified conditions inside a refractory body A, and the carbon fiber fabric B contains adhesive component c in the carbon fiber bundles b and is adhered or adhered to the refractory body A via the adhesive component c. The graphite-containing refractory of the present invention can be used as a refractory for various equipment and containers, and is particularly suitable as a lining refractory for steelmaking containers (refining containers and transport containers) used in steelworks. Examples of steelmaking containers to which the graphite-containing refractory of the present invention can be suitably applied for lining include converters, molten iron pretreatment containers such as torpedo cars and blast furnace ladles, and ladle containers. Among these, the graphite-containing refractory is particularly suitable as a lining refractory for converters, which are used in particularly severe environments, and is particularly suitable as a tuyere brick that constitutes the tuyere part. EXAMPLES
[0044] In order to study the blending of magnesia-carbonaceous raw materials for magnesia-carbonaceous refractories (graphite-containing refractories with magnesia raw materials as aggregate) used in converters, refractory molded products were produced using magnesia raw materials as aggregate with the raw material blend shown in Table 1, i.e., graphite-containing refractories without embedded carbon fiber fabric. When kneading and molding the refractory raw materials, 3 mass% of phenolic resin and 0.3 mass% of hexamine were blended as binders on an outer basis of the refractory raw materials. The melting wear resistance and cracking resistance of the graphite-containing refractories produced were evaluated using the following methods. The results are also shown in Table 1.
[0045] The corrosion resistance was evaluated based on the amount of corrosion measured by the lining method using a high-frequency induction furnace as shown in FIG. 6 (Test Method). In the test using the lining method, the test temperature was 1650°C, the temperature was held for 4 hours, and synthetic slag having the composition shown in Table 2 was added every hour. After cooling, the amount of corrosion on the working surface was measured. From the amount of corrosion, a corrosion index was calculated with the amount of corrosion of Blending Example 1-4 in Table 1 set to 100. FIG. 6(A) is an explanatory diagram showing the test implementation status in a vertical cross section of the test furnace and the cylindrical sample, FIG. 6(B) is a plan view of the cylindrical sample shown in FIG. 6(A), and FIG. 6(C) is a perspective view showing one of the test pieces constituting the cylindrical sample shown in FIG. 6(A) and (B). For crack resistance, the dynamic modulus of elasticity E0 in the longitudinal direction of a 150 mm x 150 mm x 300 mm sample was measured in accordance with the ultrasonic pulse method specified in JIS R1605, and then a cycle of heating at 1500°C for 10 minutes, water cooling for 5 minutes, and air cooling for 10 minutes was repeated three times. After these three cycles were completed, the dynamic modulus of elasticity E3 was measured again using the above method, and the rate of change in the dynamic modulus of elasticity E3 / E0 before and after the test was used as an index for evaluation.
[0046] As shown in the blending examples 1-2 to 1-8 in Table 1, when the graphite content is 1% by mass or more and 80% by mass or less, and the magnesia raw material content is 20% by mass or more and 99% by mass or less, the corrosion resistance and cracking resistance are almost constant. However, as shown in the blending example 1-1, when the graphite content is less than 1% by mass, the corrosion resistance is significantly reduced. Also, as shown in the blending example 1-9, when the magnesia raw material content is less than 20% by mass, the corrosion resistance is significantly reduced. From these, it can be seen that in order to ensure the cracking resistance of the graphite-containing refractory, it is preferable to set the graphite content to 1% by mass or more, and further, in order to achieve both corrosion resistance and cracking resistance in the blending of the magnesia-carbonaceous raw material, it is preferable to set the graphite content to 1% by mass or more and 80% by mass or less, and the magnesia raw material content to 20% by mass or more and 99% by mass or less.
[0047] The graphite-containing refractories of the invention and comparative examples, in which the carbon fiber fabric was embedded (placed) inside the refractory body A, were manufactured by the procedure shown in Fig. 3. In this case, the carbon fiber fabric was immersed in a phenolic resin (resin solution) as an adhesive in advance, and the carbon fiber fabric with the phenolic resin (sap solution) permeating and adhering to the inside and outside of the carbon fiber bundle was embedded in the refractory body. In the manufactured graphite-containing refractory, the carbon fiber fabric B was embedded along the longitudinal direction of the refractory body A as shown in Fig. 1 (in the case of multiple layers of the carbon fiber fabric B, the carbon fiber fabric B was embedded in parallel at equal intervals), and the carbon fiber fabric B contained the adhesive component c in the carbon fiber bundles b constituting it, and was adhered or bonded to the refractory body A via the adhesive component c. When the refractory raw materials were kneaded and molded, 3 mass % of phenolic resin and 0.3 mass % of hexamine were mixed as binders in the outer portion of the refractory raw materials. The produced graphite-containing refractories were evaluated for bending strength, fracture energy, resistance to melting damage, and resistance to cracking by the following methods.
[0048] As shown in Fig. 4 (Test Method), bending strength was measured using a test piece (test piece size: 150mm x 150mm x 300mm) in which carbon fiber fabric was embedded inside the refractory body along its longitudinal direction (if there were multiple layers of carbon fiber fabric, they were embedded in parallel at equal intervals), with a center distance of 100mm and a load application rate of 0.5mm / min, in accordance with the three-point bending test method described in JIS R2213. Note that Fig. 4(A) is an explanatory diagram that shows a schematic diagram of the implementation of the three-point bending strength test, and Fig. 4(B) is an explanatory diagram that shows a schematic diagram of the end face of the test piece in Fig. 4(A). As shown in Fig. 5, the fracture energy was calculated based on the position where the first peak value was shown in the load-displacement curve obtained from the three-point bending strength test, and the area within a range of 1 mm of displacement from the reference position.
[0049] The cracking resistance and corrosion resistance were evaluated by the above-mentioned method, and the test piece for evaluating the cracking resistance was one in which the carbon fiber fabric was embedded inside the refractory body along its longitudinal direction (if the carbon fiber fabric was multi-layered, it was embedded in parallel at equal intervals).The test piece for evaluating the corrosion resistance was one in which the carbon fiber fabric was embedded perpendicular to the surface (the working surface x of the refractory) that comes into contact with the slag or molten steel (if the carbon fiber fabric was multi-layered, it was embedded in parallel at equal intervals). Regarding the overall evaluation of the properties of refractory bricks, the fracture energy is 15 kJ / m 2 If the crack resistance is 0.50E3 / E0 or more, it is rated as "Excellent" (rating: ◎), and if the fracture energy is 10kJ / m 2 More than 15kJ / m 2 less than 0.40E3 / E0, and crack resistance between 0.40E3 / E0 and 0.50E3 / E0 is "good" (evaluation: ◯). Fracture energy is 10kJ / m 2 When the crack resistance was less than 0.40E3 / E0, or when the carbon fiber fabric could not be formed, the rating was "poor" (rating x).
[0050] Tables 3 to 9 show the structure and properties (flexural strength, fracture energy, resistance to corrosion, and cracking resistance) of the carbon fiber-containing magnesia-carbonaceous bricks (graphite-containing refractory material with carbon fiber fabric embedded inside the refractory body) of the invention examples and comparative examples. In these examples, the refractory body had the composition of Blending Example 1-4 in Table 1, and the maximum particle size of the aggregate (magnesia raw material) constituting the refractory body A was 3 mm. First, the examples in Table 3 examine the effects of the number of orientation directions of the carbon fiber bundles constituting the carbon fiber fabric (the number of directions in which the carbon fiber bundles are woven) and the area ratio of the carbon fiber fabric to the cross-sectional area of the refractory (the area ratio of the carbon fiber fabric to the cross-sectional area of the refractory in the cross-section of the refractory in the plane direction of the carbon fiber fabric) embedded inside the refractory body on the bending strength, fracture energy, and crack resistance of carbon fiber-containing magnesia-carbonaceous bricks.
[0051] As shown in Examples 1-1 to 1-5, when the area ratio of the carbon fiber fabric to the cross-sectional area of the refractory was 20% or more, the characteristics of the carbon fiber-containing magnesia-carbon bricks were evaluated as "excellent" or "good." On the other hand, as shown in Comparative Example 1-1, when the occupied area ratio of the carbon fiber fabric to the cross-sectional area of the refractory was less than 20%, the properties of the carbon fiber-containing magnesia-carbonaceous brick were evaluated as "poor." Furthermore, as shown in Comparative Example 1-2, when the carbon fiber bundles were oriented in only one direction, a carbon fiber fabric could not be formed, and therefore a brick with an embedded carbon fiber fabric could not be manufactured.
[0052] From these findings, it was found that the fracture energy and crack resistance of the carbon fiber-containing magnesia-carbonaceous brick can be increased by embedding a carbon fiber fabric in which carbon fiber bundles are woven in two or more directions in the refractory body and setting the area ratio of the carbon fiber fabric to the cross-sectional area of the refractory to 20% or more. It was also found that the fracture energy and crack resistance of the carbon fiber-containing magnesia-carbonaceous brick can be increased even more by setting the area ratio of the carbon fiber fabric to the cross-sectional area of the refractory to 40% or more.
[0053] The examples in Table 4 examine the effect of the thickness of the carbon fiber fabric embedded inside the refractory body on the bending strength, fracture energy, and crack resistance of the carbon fiber-containing magnesia-carbonaceous brick. As shown in Examples 1-3 and 2-2 to 2-4, when the thickness of the carbon fiber fabric was 0.1 mm or more and 3 mm or less, the characteristics of the carbon fiber-containing magnesia-carbon bricks were evaluated as "excellent." On the other hand, as shown by Examples 2-1 and 2-5, when the thickness of the carbon fiber fabric was less than 0.1 mm or more than 3 mm, the properties of the carbon fiber-containing magnesia-carbon bricks were slightly inferior to those of Examples 1-3 and 2-2 to 2-4. From the above, it was found that if the thickness of the carbon fiber fabric is between 0.1 mm and 3 mm, the fracture energy and crack resistance of the carbon fiber-containing magnesia-carbon brick can be maintained at a particularly high level.
[0054] The examples in Table 5 examine the effect of the carbon fiber bundle width w on the bending strength, fracture energy, and crack resistance of carbon fiber-containing magnesia-carbonaceous bricks for carbon fiber woven fabrics embedded inside the refractory body. As shown in Examples 1-3 and 3-2 to 3-5, when the width w of the carbon fiber bundle was more than 1 mm and not more than 15 mm, the properties of the carbon fiber-containing magnesia-carbon bricks were evaluated as "excellent." On the other hand, as shown in Example 3-1, when the width w of the carbon fiber bundle was 1 mm, the properties of the magnesia-carbon brick containing carbon fiber were slightly deteriorated. Also, as shown in Example 3-6, when the width w of the carbon fiber bundle was more than 15 mm, the properties of the magnesia-carbon brick containing carbon fiber were slightly deteriorated.
[0055] The examples in Table 6 examine the effect of the number of layers of carbon fiber fabric embedded inside the refractory body (number of embedded layers) on the bending strength, fracture energy, and crack resistance of carbon fiber-containing magnesia-carbonaceous bricks. As shown in Examples 1-3 and 5-2 to 5-4, when the number of embedded layers of carbon fiber fabric was two or more, the characteristics of the carbon fiber-containing magnesia-carbon bricks were evaluated as "excellent." On the other hand, as shown in Example 5-1, when the number of embedded layers of carbon fiber fabric was one, the characteristics of the carbon fiber-containing magnesia-carbon brick were evaluated as "good." From the above, it was found that the magnesia-carbon brick containing carbon fiber exhibits excellent properties when the number of embedded layers of carbon fiber fabric is one, and that it exhibits even better properties when two or more layers are embedded.
[0056] The examples in Table 7 examine the effect of the embedding spacing (spacing between adjacent carbon fiber fabrics) of two or more layers of carbon fiber fabric embedded inside the refractory body on the bending strength, fracture energy, and crack resistance of carbon fiber-containing magnesia-carbonaceous bricks. As shown in Examples 1-3 and 6-2 to 6-5, when the embedding interval of the carbon fiber fabric was 10 mm or more, the properties of the carbon fiber-containing magnesia-carbonaceous bricks were evaluated as "excellent." On the other hand, as shown in Example 6-1, when the embedding interval of the carbon fiber fabric was less than 10 mm, the properties of the carbon fiber-containing magnesia-carbonaceous bricks were evaluated as "good." From the above, it was found that the magnesia-carbon brick containing carbon fiber exhibits particularly excellent properties when the carbon fiber fabric is embedded at intervals of 10 mm or more.
[0057] The examples in Table 8 are for carbon fiber fabrics embedded inside the refractory body, and are carbon fiber bundles woven in the same direction. The effects of the spacing L between adjacent carbon fiber bundles on the bending strength, fracture energy and crack resistance of the carbon fiber-containing magnesia-carbonaceous bricks were investigated. As shown in Examples 1-3 and 7-1, when the interval L between adjacent carbon fiber bundles is greater than the maximum particle size (3 mm) of the aggregate constituting the refractory body, the properties of the carbon fiber-containing magnesia-carbonaceous brick are evaluated as "excellent." On the other hand, as shown in Comparative Example 7-1, when the interval L between adjacent carbon fiber bundles is equal to or less than the maximum particle size (3 mm) of the aggregate constituting the refractory body, the properties of the carbon fiber-containing magnesia-carbonaceous brick are evaluated as "poor." Note that Examples 1-3 and 7-1 also satisfy the preferred condition of the present invention that "the interval L between adjacent carbon fiber bundles is greater than 3 mm." From the above, it was found that when the distance L between adjacent carbon fiber bundles in the carbon fiber fabric is made larger than the maximum particle size of the aggregate that constitutes the refractory body, the carbon fiber-containing magnesia-carbon brick exhibits particularly excellent properties.
[0058] The examples in Table 9 examine the effect of the residual carbon ratio of the adhesive component (phenolic resin) contained in the carbon fiber bundles that make up the carbon fiber fabric and that bonds or adheres the carbon fiber fabric to the refractory body on the bending strength, fracture energy, and crack resistance of carbon fiber-containing magnesia-carbonaceous bricks. As shown in Examples 1-3, 8-2 and 8-3, when the carbon residual rate of the adhesive component was between 6% and 80%, the characteristics of the carbon fiber-containing magnesia-carbonaceous bricks were evaluated as "excellent". On the other hand, as shown in Example 8-1, when the carbon residual rate of the adhesive component was less than 6%, the characteristics of the carbon fiber-containing magnesia-carbonaceous bricks were evaluated as "good". Also, as shown in Example 8-4, when the carbon residual rate of the adhesive component was more than 80%, the characteristics of the carbon fiber-containing magnesia-carbonaceous bricks were evaluated as "good". From the above, it was found that when an organic substance is used as an adhesive component that is contained within the carbon fiber bundles of a carbon fiber fabric and that bonds or adheres the carbon fiber fabric to the refractory body, if an adhesive component with a residual carbon rate of 6% or more and 80% or less is used, the carbon fiber-containing magnesia-carbon brick will exhibit particularly excellent properties.
[0059] A similar study was also conducted on carbon fiber- and graphite-containing refractories (refractory bricks) made of alumina raw materials, silicon carbide raw materials, and silica raw materials as aggregates, which are used for linings of molten iron pretreatment vessels, etc. The examples in Table 10 examine the effects of the composition of carbon fiber-containing alumina-silica-silicon carbide-carbonaceous bricks (graphite-containing refractories made of alumina raw materials, silicon carbide raw materials, and silica raw materials as aggregates) used for the lining of molten iron pretreatment vessels on the bending strength, fracture energy, crack resistance, and corrosion resistance of the graphite-containing refractories. In this example, the carbon fiber fabric, in which the interval between adjacent carbon fiber bundles oriented in the same direction was 10 mm, was embedded in parallel at intervals of 30 mm inside an alumina-silica-silicon carbide-carbonaceous refractory (refractory body). At this time, the carbon fiber fabric was immersed in a phenolic resin (resin solution) with a residual carbon rate of 40 mass% as an adhesive in advance, and the carbon fiber fabric with the phenolic resin (resin solution) permeating and adhering to the inside and outside of the carbon fiber bundles was embedded in the refractory body. In this example, the maximum particle size of the aggregates (alumina raw material, silicon carbide raw material, silica raw material) constituting the refractory body was set to 3 mm.
[0060] As shown by Examples 9-2 to 9-8, when the content of alumina raw material was 10% by mass or more and 95% by mass or less, the content of silica raw material was 1% by mass or more and 50% by mass or less, the content of silicon carbide raw material was 1% by mass or more, and the content of graphite was 1% by mass or more and 80% by mass or less, the fracture energy was high and both high cracking resistance and high corrosion resistance were achieved. On the other hand, as shown in Example 9-1, when the alumina raw material content is less than 10 mass%, the silica raw material content is less than 1 mass%, the silicon carbide raw material content is less than 1 mass%, and the graphite content is more than 80 mass%, the fracture energy, crack resistance, and corrosion resistance are all decreased.
[0061] Furthermore, as shown in Example 9-9, when the alumina raw material content exceeds 95 mass%, the silica raw material content is less than 1 mass%, the silicon carbide raw material content is less than 1 mass%, and the graphite content is less than 1 mass%, the generation of cracks due to thermal spalling cannot be suppressed, and the fracture energy and crack resistance are reduced. From the above, it was found that in carbon fiber-containing alumina-silica-silicon carbide-carbonaceous refractories, high corrosion resistance and high fracture energy / crack resistance can be achieved simultaneously if the alumina raw material content is between 10% and 95% by mass, the silica raw material content is between 1% and 50% by mass, the silicon carbide raw material content is 1% by mass or more, and the graphite content is between 1% and 80% by mass.
[0062] The examples in Table 11 are alumina-silica-silicon carbide-carbonaceous bricks containing carbon fiber (graphite-containing refractories using alumina raw materials, silicon carbide raw materials, and silica raw materials as aggregates) used for the lining of molten iron pretreatment vessels. For graphite-containing refractories using refractory scrap obtained by crushing used alumina-silica-silicon carbide-carbonaceous refractories as part of the aggregate raw materials, the effects of the refractory scrap content on the bending strength, fracture energy, cracking resistance, and corrosion resistance of the graphite-containing refractories were investigated. In this example, the carbon fiber fabric, in which the interval between adjacent carbon fiber bundles oriented in the same direction was 10 mm, was embedded in parallel at intervals of 30 mm inside an alumina-silica-silicon carbide-carbonaceous refractory (refractory body). At this time, the carbon fiber fabric was immersed in a phenolic resin (resin solution) with a residual carbon rate of 40 mass% as an adhesive in advance, and the carbon fiber fabric with the phenolic resin (resin solution) permeating and adhering to the inside and outside of the carbon fiber bundles was embedded in the refractory body. In this example, the maximum particle size of the aggregates (alumina raw material, silicon carbide raw material, silica raw material) constituting the refractory body was set to 3 mm.
[0063] As shown in Examples 10-1 to 10-3, when the content of refractory scrap is 10% by mass or more and 90% by mass or less, the fracture energy, crack resistance, and corrosion resistance are comparable to those of the graphite-containing refractory material using only virgin raw materials shown in Table 10. On the other hand, as shown in Example 10-4, when the content of refractory scrap exceeded 90 mass %, the fracture energy, crack resistance, and corrosion resistance decreased. From the above, it was found that for carbon fiber-containing graphite-containing refractories made from refractory scrap obtained by crushing used alumina, silica, silicon carbide, and carbonaceous refractory scrap as the aggregate raw material, if the refractory scrap content is between 10% and 90% by mass, the fracture energy can be maintained high and, further, the graphite-containing refractories have the same level of cracking resistance and corrosion resistance as those made from graphite-containing refractories made only from virgin raw materials.
[0064] The examples in Table 12 examine the effects of the composition of carbon fiber-containing alumina / silicon carbide / carbonaceous bricks (graphite-containing refractories using alumina raw materials and silicon carbide raw materials as aggregates) on the bending strength, fracture energy, crack resistance, and corrosion resistance of the graphite-containing refractories. In this example, the carbon fiber fabric, in which the interval between adjacent carbon fiber bundles oriented in the same direction was 10 mm, was embedded in parallel at intervals of 30 mm inside an alumina-silicon carbide-carbonaceous refractory (refractory body). At this time, the carbon fiber fabric was immersed in a phenolic resin (resin solution) with a residual carbon rate of 40 mass% as an adhesive in advance, and the carbon fiber fabric with the phenolic resin (resin solution) permeating and adhering to the inside and outside of the carbon fiber bundles was embedded in the refractory body. In this example, the maximum particle size of the aggregate (alumina raw material, silicon carbide raw material) constituting the refractory body was set to 3 mm.
[0065] As shown in Examples 11-2 to 11-4, when the content of the alumina raw material is from 10% by mass to 95% by mass and the content of graphite is from 1% by mass to 80% by mass, high bending strength, fracture energy, crack resistance, and corrosion resistance are obtained. On the other hand, as shown in Example 11-1, when the alumina raw material content is less than 10 mass% and the graphite content is more than 80 mass%, the fracture energy, crack resistance, and corrosion resistance are decreased. Also, as shown in Example 11-5, when the alumina raw material content is more than 95 mass% and the graphite content is less than 1 mass%, the fracture energy and crack resistance are decreased. From the above, it was found that in carbon fiber-containing alumina / silicon carbide / carbonaceous refractories, if the alumina raw material content is between 10% and 95% by mass, and the graphite content is between 1% and 80% by mass, then high fracture energy, crack resistance, and corrosion resistance can be obtained.
[0066] The examples in Table 13 examine the effects of the composition of carbon fiber-containing silica / silicon carbide / carbonaceous bricks (graphite-containing refractories using silica raw material and silicon carbide raw material as aggregates) on the bending strength, fracture energy / crack resistance, and corrosion resistance of the graphite-containing refractories. In this example, the carbon fiber fabric, in which the interval between adjacent carbon fiber bundles oriented in the same direction was 10 mm, was embedded in parallel at intervals of 30 mm inside a silica-silicon carbide-carbonaceous refractory (refractory body). At this time, the carbon fiber fabric was immersed in a phenolic resin (resin solution) with a residual carbon rate of 40 mass% as an adhesive in advance, and the carbon fiber fabric with the phenolic resin (resin solution) permeating and adhering to the inside and outside of the carbon fiber bundles was embedded in the refractory body. In this example, the maximum particle size of the aggregate (silica raw material, silicon carbide raw material) constituting the refractory body was set to 3 mm.
[0067] As shown by Examples 12-2 to 12-4, when the content of the silica raw material was 1 mass % or more and 50 mass % or less, high bending strength, fracture energy, crack resistance, and corrosion resistance were obtained. On the other hand, as shown in Example 12-1, when the content of the silica raw material is less than 1 mass %, the fracture energy and crack resistance decrease. Furthermore, as shown in Example 12-5, when the content of the silica raw material exceeds 50 mass %, the generation of cracks due to thermal spalling cannot be suppressed, and the fracture energy and crack resistance decrease. From the above, it was found that in carbon fiber-containing silica / silicon carbide / carbonaceous refractories, if the content of silica raw material is between 1% by mass and 50% by mass, high bending strength, fracture energy, crack resistance, and corrosion resistance can be obtained.
[0068] Table 14 shows the results of evaluating the wear rate of the brick of the present invention in Example 1-3 (graphite-containing refractory material with magnesia raw material as aggregate) and a conventional brick with no embedded carbon fiber fabric installed in the tuyere of a converter. The conventional brick has the same composition and is manufactured by the same method as the brick of the present invention in Example 1-3, except that no embedded carbon fiber fabric is installed. As shown in Table 14, the wear rate of the brick of the present invention was reduced by 50% or more compared to the conventional brick. Table 15 shows the results of evaluating the wear rate of the brick of the present invention in Example 1-3 (graphite-containing refractory material with magnesia raw material as aggregate) and a conventional brick with no embedded carbon fiber fabric installed on the side wall of a ladle slag line. The conventional brick has the same composition and is manufactured by the same method as the brick of the present invention in Example 1-3, except that no embedded carbon fiber fabric is installed. As shown in Table 15, the wear rate of the brick of the present invention was reduced by 50% or more compared to that of the conventional brick.
[0069] Table 16 shows the results of evaluating the wear rate of the inventive brick of Example 9-5 (graphite-containing refractory material with aggregates of alumina raw materials, silicon carbide raw materials, and silica raw materials) and a conventional brick with no embedded carbon fiber fabric, which were installed on the side wall of a blast furnace ladle, a vessel for pre-treating molten iron. The conventional brick had the same composition and was manufactured by the same method as the inventive brick of Example 9-5, except that no embedded carbon fiber fabric was used. As shown in Table 16, the wear rate of the inventive brick was reduced by about 20% to 30% compared to the conventional brick. As shown in Tables 14 to 16, it was found that when the brick of the present invention is applied to a converter, a ladle, or a molten iron pretreatment vessel, the wear rate of the actual equipment can be significantly reduced.
[0070] [Table 1]
[0071] [Table 2]
[0072] [Table 3]
[0073] [Table 4]
[0074] [Table 5]
[0075]
Table 6
[0076]
Table 7
[0077]
Table 8
[0078]
Table 9
[0079]
Table 10
[0080]
Table 11
[0081]
Table 12
[0082]
Table 13
[0083]
Table 14
[0084]
Table 15
[0085] [Table 16] [Explanation of symbols]
[0086] A Refractory body B Carbon fiber fabric c Adhesive component b Carbon fiber bundle x Refractory working surface y Counter moving surface
Claims
1. A graphite-containing refractory for use as a refractory lining for steel vessels, comprising: A graphite-containing refractory having a graphite-containing refractory body (A) and a carbon fiber fabric (B) in which carbon fiber bundles (b) are woven in two or more directions, embedded therein, The carbon fiber fabric (B) is embedded in two or more layers in parallel at intervals in a direction perpendicular to a refractory operating surface inside the refractory body (A), and the interval between adjacent carbon fiber fabrics (B) is 10 mm or more; The carbon fiber fabric (B) contains an adhesive component (c) in the carbon fiber bundles (b) and is adhered or in close contact with the refractory body (A) via the adhesive component (c); The carbon fiber bundles (b) arranged in the same direction constituting the carbon fiber fabric (B) have an interval between adjacent carbon fiber bundles (b) that is larger than the maximum particle size of the aggregate constituting the refractory body (A) and an interval between adjacent carbon fiber bundles (b) that is more than 3 mm and not more than 50 mm; In a cross section of the refractory in a plane direction of the carbon fiber fabric (B), the area ratio of the carbon fiber fabric (B) to the cross-sectional area of the refractory is 40% or more; The thickness of the carbon fiber fabric (B) is 0.1 mm or more and 3 mm or less, The width of the carbon fiber bundles (b) constituting the carbon fiber fabric (B) is more than 1 mm and 15 mm or less, Graphite-containing refractory material, characterized in that the adhesive component (c) is a phenolic resin.
2. 2. The graphite-containing refractory material according to claim 1, wherein the adhesive component (c) is an organic substance having a residual carbon rate of 6 mass % or more and 80 mass % or less.
3. 3. The graphite-containing refractory according to claim 1 or 2, characterized in that the refractory body (A) has a graphite raw material content of 1 mass % or more and 80 mass % or less.
4. 4. The graphite-containing refractory according to claim 1, wherein the refractory body (A) has a magnesia raw material content of 20% by mass or more and 99% by mass or less.
5. 5. The graphite-containing refractory according to claim 1, wherein the refractory body (A) has an alumina raw material content of 10% by mass or more and 95% by mass or less.
6. The graphite-containing refractory according to any one of claims 1 to 3 and 5, characterized in that the refractory body (A) has a silica raw material content of 1 mass% or more and 50 mass% or less.
7. 7. The graphite-containing refractory according to claim 5 or 6, characterized in that the refractory body (A) has a silicon carbide raw material content of 1 mass % or more.
8. The graphite-containing refractory according to any one of claims 1 to 7, characterized in that the refractory body (A) contains refractory chips obtained by pulverizing used refractories in an amount of 10 mass% to 90 mass% as a refractory raw material.
9. A converter comprising the graphite-containing refractory material according to any one of claims 1 to 8.
10. A molten iron pretreatment vessel comprising the graphite-containing refractory material according to any one of claims 1 to 8.
11. A ladle vessel comprising the graphite-containing refractory material according to any one of claims 1 to 8.
Citation Information
Patent Citations
Ceramic flamed matter and manufacture
JP1983026082A
Refractory brick
JP1984156970A
Manufacture of ceramic formed body
JP1987162675A
High-strength refractory
JP1996012456A
Refractory having excellent mechanical strength and spalling resistance, and method of manufacturing the same
JP2005320196A